Increasing Individual Taxpayer Compliance by Taxpayer Awareness: Study at one of the KPPs in Bandung City - Putri Rahayu Dwiningtyas; Iwan Sidharta; Haritsatun Najwa; Octaviane Herawati (P3M, STIE Pasundan, Bandung, Indonesia., 2023)
The objectives of this study were to ascertain and examine the level of taxpayer awareness, individual taxpayer compliance, and the impact of taxpayer awareness on individual taxpayer compliance at the Pratama Tax Office. The employed data analysis techniques encompassed descriptive analysis and verification analysis. The data collection methodology employed in this study entailed disseminating questionnaires to tax officials at a specific Pratama Tax Office in Bandung City. The sample consisted of 40 individuals who were directly involved in the subject matter under investigation. The study employed the Exhaustive Sampling (Census) technique under Nonprobability Sampling. The research findings revealed that the product-moment correlation analysis yielded a coefficient of 0.860, indicating a highly significant and robust relationship between the variables. The results of the simple linear regression analysis indicate that there is a positive relationship between Taxpayer Awareness and Individual Taxpayer Compliance. The equation derived from the analysis is Y = 8.305 + 0.834X, where Y represents the level of Individual Taxpayer Compliance, and X represents Taxpayer Awareness. The coefficient of determination, which measures the proportion of variance in Individual Taxpayer Compliance (Y) explained by Taxpayer Awareness, is 0.739. This condition indicates that Taxpayer Awareness has a significant influence of 73.9% on Individual Taxpayer Compliance. The remaining 26.1% of the variance in Individual Taxpayer Compliance is attributable to other factors not examined in this study, including tax amnesty, e-filing, tax audits, tax penalties, tax bills, and other relevant variables.